Students Perceptions of Operations Research Learning During the Covid-19 Pandemic with Realistic Mathematics Educations Approach - Roswita Hafni; Zulia Hanum; Lailan Safina Hasibuan (Journal of International Conference Proceedings (JICP), 2021)
Operations Research is a quantitative decision–making course, which is formed in a mathematical model by allocating limited resources, so that the goal is optimal. The purpose of this study was to determine students’ perceptions of Operations Research learning during the covid–19 pandemic in order to apply the Realistic Mathematics Educations approach in developing Operations Research teaching materials. The research method was conducted by questionnaire with the number of respondents as many as 91 college students. The results showed that the students’ perceptions of Operations Research learning with indicators of feeling of pleasure, feeling of interest, general impact, and motivation, were in the high category with percentages of 42,86%, 62,64%, 42,86%, and 51,65%. Based on the results of the study, this can increase resources, both qualified lecturers and students and the realization of quality higher education to produce graduates who are knowledgeable, educated, and skilled. Thus, there are several factors that must be improved, such as the availability of facilities, lecturers, learning materials presented using video as an application of the model in the real life, and field studies.